The long-term antibody response after SARS-CoV-2 prime-boost vaccination in healthy individuals: The positive influence of extended between-dose intervals and heterologous schedule - Naidich, Gretel (2023)
Introduction: Anti-COVID vaccination in Argentina was carried out using different protocols and variations in periods between administrations, as well as combinations of different vaccine platforms. Considering the relevance of the antibody response in viral infections, we analyzed anti-S antibodies in healthy people at different points of time following the Sputnik immunization procedure. Methods: We attended the vaccination centers in the city of Rosario, which had shorter versus longer intervals between both doses. A total of (1021) adults with no COVID-compatible symptoms (throughout the study period) were grouped according to the gap between both vaccine doses: 21 (Group A, n=528), 30 (Group B, n=147), and 70 days (Group C, n=82), as well as an additional group of individuals with heterologous vaccination (Sputnik/Moderna, separated by a 107- day interval, group D, n=264). Results and conclusions: While there were no between-group differences in baseline levels of specific antibodies, data collected several weeks after administering the second dose showed that group D had the highest amounts of specific antibodies, followed by values recorded in Groups C, B, and A. The same pattern of group differences was seen when measuring anti-S antibodies at 21 or 180 days after the first and second doses, respectively. Delayed betweendose intervals coexisted with higher antibody titers. This happened even more when using a prime-boost heterologous schedule.